2019
DOI: 10.1016/j.knee.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Are patient-related pre-operative factors influencing return to work after total knee arthroplasty

Abstract: Background: Osteoarthritis is one of the leading causes of disability in working-age patients. The total number of working-age patients undergoing total-knee arthroplasty (TKA) is continuously increasing. The purpose of this study was to identify predictive factors related to general health, health risk behaviors and socioeconomic status influencing the rate of return to work after a TKA. Methods: Overall there were 151,901 patients included in the Finnish Public Sector (FPS) study. The response rate varied be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…BMI was also not found to have a statistically significant relationship with RTW. The current results partly agree with previous reports on the one hand, but are also in contrast to other findings 7,12,14,15,17,22 . Nevertheless, all modifiable potential risk factors should be accounted for when planning THA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…BMI was also not found to have a statistically significant relationship with RTW. The current results partly agree with previous reports on the one hand, but are also in contrast to other findings 7,12,14,15,17,22 . Nevertheless, all modifiable potential risk factors should be accounted for when planning THA.…”
Section: Discussionsupporting
confidence: 92%
“…The RTW time of this study is in line with previous studies. RTW after THA ranged from 1 to 10 weeks after surgery and the post-surgical proportion of patients that returned to work ranged from 25 to 95% 7,[12][13][14][15][16][17] . Considering these results, the majority of patients employed before their THA resumed work postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…However, higher RTW rates were reported in other studies where the majority of patients also had manual jobs (52% manual jobs and 87% RTW). 18 Moreover, Scott et al could not find any statistically significant correlation between heavy-or moderate-manual work and RTW (p ¼ 0.03). It also has to be noted that this study has the highest mean age among included studies, and that in this study, the majority of patients not returning to work was aged >60 years.…”
Section: Discussionmentioning
confidence: 92%
“…Six studies found significant correlation while applying multivariate analysis. [11][12][13][14]18,19 Four studies did not perform any statistics but mentioned preferences or influencing factors reported by patients to be influencing their RTW. 9,10,16,17 Factors shown to be correlated with RTW by multivariate analysis were the physical nature of employment (p ¼ 0.03, 14 0.012, 11 and <0.0001 12,18 ), preoperative absence from work (p < 0.0001 18 and0.001 19 ), flexible work conditions Return to Work after Primary TKA at below 65 Years Van Leemput et al…”
Section: Associated Factorsmentioning
confidence: 99%
“…Our findings suggest that preoperative PA level is not an important parameter for healthcare professionals to predict time to RTW after THA and TKA. A recent longitudinal study among TKA patients also found that patients that were in many ways in better physical shape did not return to work earlier than other patients [54]. To our knowledge these are the first two prospective studies to evaluate the association between PA level in daily life and time to RTW after THA and/or TKA.…”
Section: Discussionmentioning
confidence: 99%